Influence of Lifestyle on the Health Status of Students of Tertiary Institutions in Benue State, Nigeria. - Sewuese, Iorvaa (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
Lifestyle and its effects on health has been the subject of interest recently. Living a healthy lifestyle and having a decreased risk of killer diseases is of utmost importance. This study examined the influence of dietary intake, sexual behaviour and physical activity as lifestyle on the health status of tertiary institution students in Benue State, Nigeria. The descriptive survey design was adapted for the study; Samples of 685 respondents were randomly selected from a total population of 13,992 students. Data were collected using a self-developed and validated questionnaire with the reliability of 0.742 Cronbach Alpha. Frequency counts, percentages and chi square were used to analyze the generated data. The study found out that dietary intake (x2=338.445,df=3,p<0.05),sexual behaviour (x2=680.133,df=3, P<0.05) and physical activity (x2=520.670,df=3, P<0.05) had significant influence on the health status of students of tertiary institutions in Benue state. The researcher therefore, recommended that students should be properly educated on effects of lifestyle such as dietary intake, sexual behaviour and physical activity on their health status thereby taking informed decision to avoid negative lifestyle